VIRTUAL AND AUGMENTED REALITY IN MODERN EDUCATION: IMPROVING LEARNING QUALITY AND ENGAGEMENT - Risqah Amaliah Kasman; Yudhi Priyatmo; Andi Evi Sulfiyani Nurfathanah Amsal (INJOSEDU: International Journal of Social and Education, 2026)
The use of Virtual Reality (VR) and Augmented Reality (AR) technologies has emerged as an important innovation in modern education by creating immersive and interactive learning experiences. This study aims to analyze previous research on the role of VR and AR in improving learning quality and student engagement in the digital age. The research employs a qualitative approach, using library research to review scholarly articles and academic publications on immersive learning technologies. The findings indicate that VR and AR technologies enhance students’ conceptual understanding and engagement through realistic simulations and interactive visualization. However, successful implementation depends on pedagogical design, technological infrastructure readiness, and educators’ ability to effectively integrate immersive technologies into learning environments. The study highlights the importance of aligning technological innovation with instructional strategies to optimize learning outcomes in modern education systems.